Answer:
Step-by-step explanation:
Answer:
<h2>
![x = - \frac{17}{4}](https://tex.z-dn.net/?f=x%20%3D%20%20-%20%20%5Cfrac%7B17%7D%7B4%7D%20)
</h2>
Step-by-step explanation:
![6x + 3(4x - 2) = 5(2x - 8)](https://tex.z-dn.net/?f=6x%20%2B%203%284x%20-%202%29%20%3D%205%282x%20-%208%29)
Expand the terms in the bracket and simplify
That's
![6x + 12x - 6 = 10x - 40 \\ 18x - 6 = 10x - 40](https://tex.z-dn.net/?f=6x%20%2B%2012x%20%20-%206%20%3D%2010x%20-%2040%20%5C%5C%2018x%20-%206%20%3D%2010x%20-%2040)
Using the subtraction property subtract 10x from both sides of the equation
![18x - 10x - 6 = 10x - 10x - 40 \\ 8x - 6 = - 40](https://tex.z-dn.net/?f=18x%20-%2010x%20-%206%20%3D%2010x%20-%2010x%20-%2040%20%5C%5C%208x%20-%206%20%3D%20%20-%2040)
<u>Add 6 to both sides of the equation</u>
![8x + 6 - 6 = - 40 + 6 \\ 8x = - 34](https://tex.z-dn.net/?f=8x%20%2B%206%20-%206%20%3D%20%20-%2040%20%2B%206%20%5C%5C%208x%20%3D%20%20-%2034)
<u>Divide both sides by 8</u>
![\frac{8x}{8} = - \frac{34}{8}](https://tex.z-dn.net/?f=%20%5Cfrac%7B8x%7D%7B8%7D%20%20%3D%20%20-%20%20%5Cfrac%7B34%7D%7B8%7D%20)
<u>Reduce the fraction with 2</u>
We have the final answer as
![x = - \frac{17}{4}](https://tex.z-dn.net/?f=x%20%3D%20%20-%20%20%5Cfrac%7B17%7D%7B4%7D%20)
Hope this helps you
Answer:
D. 14
Step-by-step explanation:
4^2 - 2 (evaluate)
16 - 2 (calculate)
14
Step-by-step explanation: 13.93 + 7.37 = 21.3 14 + 7 = 21